Splitting upconversion emission and phonon‐assisted population inversion of Ba2Y(BO3)2Cl:Yb3+, Er3+ phosphor. Issue 11 (31st July 2017) - Huang, Anjun; Yang, Zhengwen; Yu, Chengye; Qiu, Jianbei; Song, Zhiguo
Abstract: Upconversion (UC) peak of 4 S3/2 → 4 I15/2 transition of Er 3+ is close to that of 2 H11/2 → 4 I15/2 transition. The UC emission splitting of Er 3+ caused by coordination fields of host results in that it is difficult to confirm which transitions ( 4 S3/2 → 4 I15/2 or 2 H11/2 → 4 I15/2 ) are responsible for the splitting UC emission peaks. In this work, the UC luminescence peaks located at 524, 540, 551, 565, 662, 677, and 683 nm were observed in the Ba2 Y(BO3 )2 Cl:Yb 3+, Er 3+ phosphor upon the 980 nm excitation. The 524 and 540 nm UC emissions intensity were increased, while the 551 and 565 nm UC emissions intensity were decreased with the temperature increasing from 323 to 573 K, which is attributed to the phonon‐assisted population inversion from the 4 S3/2 to 2 H11/2 level. The temperature dependence of UC emission spectra demonstrated that the 524 and 540 nm UC emissions are from 2 H11/2 → 4 I15/2 transition, and 551 and 565 nm UC emissions are from the 4 S3/2 → 4 I15/2 transition. Temperature sensing property was characterized by the UC intensity ratio of the 2 H11/2 → 4 I15/2 transition to 4 S3/2 → 4 I15/2 transition. The Ba2 Y(BO3 )2 Cl:Yb 3+, Er 3+ phosphor has potential application as the non‐contact temperature sensor.